PERAN SUPERVISOR MADRASAH DALAM MENINGKATKAN KINERJA KEPALA MADRASAH DAN GURU DI MTSS AL-HIDAYAH DAN MTSN 10 CIAMIS - HUJAEMAH (UNISAN JURNAL, 2024)
The world of education cannot be separated from the responsibility of all parties, be it the government, parents, and the community. Because if education is not handled or no one is responsible, it is feared that in the future our education will be increasingly unclear. Therefore, it needs very serious attention, especially from the government that carries this responsibility to supervisors, because when an educational institution gets serious supervision, it is hoped that a quality education will be created, especially if it is carried out by an expert supervisor. Therefore, the supervisor’s role is very supportive, because without an expert supervisor (professional) it is impossible for a school/madrasa to run well and with quality. This research was conducted on the basis of the fact that the performance problems of principals and teachers still require serious attention, because their performance is influenced by supervision. This study uses a qualitative descriptive approach located at MTSS Al-Hidayah dan MTSN 10 Ciamis. Sources of information in this study were school supervisors, principals, and teachers. The instruments used to explore data sourced from (1) observations or observations, (2) interviews, and (3) documentation. Data analysis was carried out in three stages, namely data reduction, data display and verification. The conclusion from this research is that the role of supervision carried out by supervisors in improving the performance of the madrasa principal and supervision is carried out well and is able to make a positive contribution to the school. In addition, the principal can openly be protected by supervisors in terms of supervision so that they are able to apply in mobilizing, improving, and giving a positive influence on teachers to improve their performance, so that at an advanced stage it can affect the quality of learning.